“Greenlandicness” and Nation Building in Kalaallit Nunaat - Thomsen, Robert (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2023)
Greenland is in the process of full de-colonization and is moving towards independence as the first Inuit nation-state. This trajectory, which is influenced by a widespread sense of nationhood, appears to set Greenland apart from other Inuit communities in the Arctic. This article investigates the nature and role of understandings of “Greenlandicness” in Kalaallit Nunaat (Greenland), as well as their effects on contemporary nation building and visions for a future independent Greenland. It explores past and current debates about collective identity in Greenland by analysing political discourses as expressed in mass and social media, Inatsisartut debates and official documents, and various statements by politicians, parties, and Naalakkersuisut. The discourse analysis is inspired by Wetherell and Potter’s social psychology approach to identity analysis, including their understanding of “interpretative repertoires” (1988). The article concludes that although Indigeneity remains one source of the perception of the inherent right of the Greenlandic people to self-determination, the stronger current in Greenland politics and collective identification is one of classical (European) nationalism. Further, it finds that a number of discursive repertoires exist, which can be thematically labelled: Kalaallit Indigenous nationalism, pan-Inuit Indigenism, post- and de-colonialism, (post-)modernism, traditionalism, and ethnic and civic nationalism.